Group Exhibition-Supernova-Constellations, The Nicosia Municipal Art Center associated with The Pierides Foundation and the British Council - Antoniou, Klitsa (My University, 2026)
Supernova-Constellations, The Nicosia Municipal Art Center associated with The Pierides Foundation and the British Council, London Curated by Yiannis Toumazis